An Analysis of Factors Affecting Dropout Risks of Nontraditional Students: Evidence from U.S. 4-Year Commuter Institutions. Issue 1 (January 2020) - Chen, Jin; Ziskin, Mary B.; Torres, Vasti
Utilizing event history analysis and multilevel models, this study explored dropout risks for first-time nontraditional students who started at public 4-year commuter institutions across a U.S. Midwest state. The study revealed that (a) the dropout hazard rate remained relatively high across college years and differed by gender, race, and family income; (b) individual characteristics such as socioeconomic backgrounds, academic performance and financial need were significant predictors for dropout, and (c) the differences in dropout were largely attributable to institutional structural and resource differences. These findings have important implications for policies and practices aiming to promote nontraditional student persistence to graduation.